Essential Guide of Analysis Methods Applied to Silver Complexes with Antibacterial Quinolones - Aura Rusu; Gabriel Hancu; Silvia Imre (Tabriz University of Medical Sciences, 2018)
To describe the chemical structure and characterize physico-chemical properties of organometallic complexes it is necessary to use a complex set of analysis methods. Thus, this review has been compiled as a relevant guide which includes the most commonly used methods of analysis in the study of silver complexes with antibacterial quinolones, compounds with promising biological potential. This selection of analysis methods puts on balance the obtained data and the accessibility of the experimental approach. The steps to follow in order to obtain reliable structural information about organometallic complexes of silver, particularly the silver complexes of antibacterial quinolones, are established and presented in the review.